Gyromagnetic ratio of higher dimensional black holes - Kaya, R. (IOP PUBLISHING LTD, 2008)
We consider a rotating black hole with two angular momenta in D=6 dimensions and three angular momenta in D=7 dimensions. Using Wald's test field approach we derive the solution for the electromagnetic field occurring when the black hole is placed in a uniform magnetic field. It is shown that a weakly charged rotating black hole in D=6 and 7 dimensions possesses two and three independent magnetic dipole moments, respectively. We conjecture that the gyromagnetic ratio of a D-dimensional weakly charged Myers - Perry black hole possesses the value g=D - 2.
Keywords: MAGNETIC UNIVERSE; FIELD; MILLIMETER; HIERARCHY; MASS; Astronomy & Astrophysics; Physics